Nutritional quality, degradability and methane production in silvopastoral arrangements - Liliana Mahecha-Ledesma; Joaquín Angulo-Arizala; Wilson Ándres Barragán-Hernández (Agronomía Mesoamericana, 2017)
The aim of this work was evaluate the bromatological quality, the degradability of dry matter and the mitigation potential of the forage from the different silvopastoral arrangements in three shade levels (0, 30 y 60%). This study was carried out between October 2012 and September 2013, in the La Candelaria farm from the Antioquia University, Colombia. The arrangements contained within Brachiaria grasses (Brachiaria brizantha cv toledo, Brachiaria decumbens and Brachiaria hibrido cv mulato II) alone or associated with Tithonia diversifolia and Cratilya argentea in silvopastoral arrangements. Evaluation was made in forage of forty days, the chemical composition, content of polyunsaturated fatty acids, degradation of dry matter and in vitro methane production were determined. The arrangement used (grass alone or associated with shrubs affected signi cantly the concentration of protein and linoleic acid (p<0.05). Not effect was observed in the arrangement, level of shade and interaction arrangement x shade in the degradability of dry mater after 48 h (p>0.05). However, pre-planned comparisons indicated that the association of Brachiaria brizantha cv toledo with shrubs improved the degradability of dry matter (MS) at 48 h, and was observed that the interaction shade x arrangement affected the dynamic degradation of MS. The factors evaluated (arrangement and shade) did not affect the in vitro methane emission.